2004
DOI: 10.1167/iovs.04-0326
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondiiInfection in Animal-Friendly Pig Production Systems

Abstract: The following conclusions may be derived from this study: Conventionally (indoors) raised pigs are free from Toxoplasma infection, and (2) animal-friendly production systems may lead to a reemergence of Toxoplasma infections, although many of these farms remain Toxoplasma free. Slaughterhouse monitoring of pigs from animal-friendly production systems combined with on-farm prevention strategies should be applied to ensure safety for consumers of the meat products obtained from these animals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
69
0
8

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(81 citation statements)
references
References 14 publications
0
69
0
8
Order By: Relevance
“…Corresponding to that, a low (0.0-0.4%) to moderate (36%) prevalence was estimated on conventional pig farms in European countries [43,48]. In the USA, a higher (25%) prevalence was detected in the free range animals than in the outdoor-(6.8%) or indoor-ranged finishers (2.8%) [46,51].…”
Section: Prevalence Of T Gondii In Domestic Pigmentioning
confidence: 86%
See 1 more Smart Citation
“…Corresponding to that, a low (0.0-0.4%) to moderate (36%) prevalence was estimated on conventional pig farms in European countries [43,48]. In the USA, a higher (25%) prevalence was detected in the free range animals than in the outdoor-(6.8%) or indoor-ranged finishers (2.8%) [46,51].…”
Section: Prevalence Of T Gondii In Domestic Pigmentioning
confidence: 86%
“…Hence, organic pigs are mainly reared outdoor, receive an organic feed, are provided with an animal friendly living space, the piglets are weaned at the later age than 3-4 weeks as on the intensive farms, and undergo a restrictive use of the antibiotics. The free range pigs differ from the regular pigs by the outdoor access and straw bedding, but are fed with a standard porcine feed and may receive drug treatment, if necessary, without losing a label as in case of the organic pigs [43]. In both types of farming, pigs are continuously exposed to the parasite by contact with contaminated soil or ground water, and can easily transmit the infection further in the food chain [43,44,74].…”
Section: Risk Factors Associated With the Porcine Toxoplasmosismentioning
confidence: 99%
“…For this reason pork meat is no longer a major source of infection as in the past. However, the present trend to the so-called organic animal raising, or animal-friendly farming, needs to be kept in mind as it could lead to a recrudescence of infection in pigs (Kijlstra et al, 2004). Recent trends in consumer habits, in fact, indicate a shift toward consumption of animal-friendly or organic pigs, which include increased exposure of the pig to the environment, and this will lead to an increased risk of T. gondii in products from such animals (Hill et al, 2010).…”
Section: Ingestion Of Infected Tissuesmentioning
confidence: 99%
“…Noteworthy, increasing animal-friendly production systems might increase T. gondii prevalence if cooking practice is not proper. Chumpolbanchorn et al (2009) demonstrated 64.03% T. gondii antibody in Thai free-range chickens, while low prevalence (2.3%) was found in animal-friendly pig production systems in the Netherlands (Kijlstra et al, 2004). Limiting exposure to cats, their litter and soil contamination with cat fecaes are things to be practised as well as avoiding infective oocysts by daily disposal cat litter and thorough hand washing, keeping cats indoor and feeding with canned or well-cooked food.…”
Section: Preventive Measuresmentioning
confidence: 99%